Multidrug-resistant mycobacterium tuberculosis of the Latin American mediterranean lineage, wrongly identified as mycobacterium pinnipedii (Spoligotype International Type 863 [SIT863]), causing active tuberculosis in South Brazil - Dalla Costa, Elis R. (2018)
PMID: 26400784 WOS:000367532800016